Musicalization of Literature: Kostas Ostrauskas’s The Quartet - Smolskaitė, Giedrė (Semiotika, 2017)
In works of literature, music can be found in the form of score fragments, notation symbols, song lyrics, musicological terminology, acoustic aspects of speech, musicians as characters, etc. Such manifestations connect two systems of signification and create an intermedial dialogue between music and literature, which requires a specific methodological approach. According to the intermediality theoretician Werner Wolf, “[t]he verbal text appears to be or become [...] similar to music, or to effects connected with certain compositions, and we get the impression of experiencing music ‘through’ the text”26. This paper discusses possible forms of a musico-literary relationship, the effects they produce, and examples of musicalization found in Kostas Ostrauskas’s play The Quartet (1969). In this play, the musico-literary dialogue is developed on different levels: structure and story, the twofold nature of the characters, intertextuality. Analysis of the play’s architextual relationship with the medium of music helps to identify the specific, musico-literary genre of this play. This unusual genre is defined not only by the content of The Quartet but also by its expression, i.e. graphic nuances, inserted imagery, etc. As shown by the analysis, the play could be understood as a metonymy of the history of both contemporary music and dramatic literature.
Keywords: musicalization of literature; intermediality; Ostrauskas